Responsabilidad de empleadores y trabajadores frente al acoso laboral y otros hostigamientos en el marco de las relaciones de trabajo subordinado (2009)
The labor harassment regulation, consecrated in Law 1010 on the 23rd January of 2006, is analyzed in light of constitutional rules – equality and respect to the human dignity –, trying to identify diverse types of responsibility that have as a source the damage to the person of relations of work within the framework subordinated, which they are put under all the workers of private or public organizations, that can have the double condition for being active object of harassment (victims) or subjects of the same (pursuing). The academic reflections, product of this process of investigation fall on the interpretation and scope of application that becomes of the new law to determine the basic elements of the civil or penal responsibility, with the purpose of to contribute to their spreading and knowledge.